Behavioral analysis on IPv4 malware on different platforms in IPv6 network environment - M., Zulkiflee; Asmai, Siti Azirah; N., Haniza; Ayop, Zakiah; Sahib@Sahibuddin, Shahrin (2011)
Malware is becoming an epidemic in computer network nowadays. Malware attacks are a significant threat to networks. A conducted survey shows malware attacks may result a huge financial impact. This scenario has become worse when users are migrating to a new environment which is Internet Protocol Version 6. In this paper, a real Nimda worm was released on a network to further understand the worm behavior in real network traffic. A controlled environment of IPv6 networks were deployed as a testbed for this study. The result between these two scenarios on different operating system platforms will be analyzed and discussed further in term of the worm behavior. The experiment result shows that even IPv4 malware still can infect the IPv6 network environment without any modification on the existing malware. In addition, the worm behaves differently in different operating system. A statistical approach will be used to validate the result. New detection techniques need to be proposed to remedy this problem swiftly.